ANALYSIS OF THE IMPLEMENTATION OF SFAS No. 102 REVISED 2013 IN FINANCING MURABAHAH MANDIRI SYARIAH BANK BRANCH PONTIANAK 2015 - B41112116, Karisa Claudia Runtu (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACTThe house is one of the primary needs, but many factors that make it difficult for the Indonesian people to have a dream home. Bank loans granted to get a house may be the wisest way to be able to get a place to stay. As the development of economy in Indonesia, Bank Syariah Mandiri issued mortgages products are better known by the term Financing Griya BSM with murabahah which regulates the sale and purchase with Islamic law. But in fact a lot of mismatches in the murabaha contract application of Islamic Financial Institutions, the DSN MUI fatwa was issued No. 84, DSN-MUI / XII / 2012 and the subsequent changes in the rules of SFAS No. 102 2007 became SFAS No. 102 revision in 2013.The purpose of this study was to determine whether the Bank Syariah Mandiri has adopted SFAS No. 102 (2013) and to find out how the accounting treatment at Bank Syariah Mandiri in providing financing home ownership. This study used descriptive qualitative method where researchers conducted interviews to the parties involved and get a good data source of primary data and secondary data.The results of this study, firstly, the banks have not fully adopted SFAS No. 102 in 2013 and their revision in the agreement wakalah murabaha. Second, the bank does not act as a seller but as a provider of financing funds. Thirdly, the presentation of murabaha receivables in accordance with SFAS No. 102, 2013 and the last revision, disclosure and accounting treatment as the advances and fines in accordance with SFAS No. 102 revision in 2013.Keywords: Murabahah Accounting, SFAS No. 102 2007, SFAS No. 102 revision in 2013